Proceedings of the 1st ACM International Workshop on Vehicular Ad Hoc Networks 2004
DOI: 10.1145/1023875.1023877
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of safety applications over DSRC vehicular ad hoc networks

Abstract: In this paper we conduct a feasibility study of delay-critical safety applications over vehicular ad hoc networks based on the emerging dedicated short range communications (DSRC) standard. In particular, we quantify the bit error rate, throughput and latency associated with vehicle collision avoidance applications running on top of mobile ad hoc networks employing the physical and MAC layers of DSRC. Towards this objective, the study goes through two phases. First, we conduct a detailed simulation study of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
192
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 370 publications
(193 citation statements)
references
References 24 publications
1
192
0
Order By: Relevance
“…On these channels, safety messages have a higher priority over non-safety messages in order to guarantee the reliability of safety applications. A more detailed discussion on DSRC can be found in [28,29].…”
Section: Dedicated Short-range Communications (Dsrc)mentioning
confidence: 99%
See 1 more Smart Citation
“…On these channels, safety messages have a higher priority over non-safety messages in order to guarantee the reliability of safety applications. A more detailed discussion on DSRC can be found in [28,29].…”
Section: Dedicated Short-range Communications (Dsrc)mentioning
confidence: 99%
“…Many efforts have been made to bring the promising technology to fruition. The study of characterizing and enhancing the performance of DSRC/WAVE can be found in [5,16,29,31,32].…”
Section: Dedicated Short-range Communications (Dsrc)mentioning
confidence: 99%
“…7. According to the dedicated short-range communication (DSRC) specifications, each wireless data channel in VANET has a bandwidth of 10 MHz that corresponds to a channel data rate in the range of 3-27 Mb/s [31]. We select a data rate of 6 Mb/s for the wireless channels in a VANET.…”
Section: Revocation Delaymentioning
confidence: 99%
“…Most of these applications rely on single-hop communication and their effectiveness is evaluated based on two key aspects: success of delivery and the practical benefit [1]. It is worth noting that VCPS has a human element in the loop since the driver is the final control unit for all generated information.…”
Section: Introductionmentioning
confidence: 99%